Evaluation of the Family Planning Programme in India Report of the Panel of Consultants - Planning Commission (Planning Commission, 1965)
On the recommendation of the Central Family Planning Board, the Ministry of Health of the Government of India constituted the Family Planning Programme Evaluation and Planning Committee towards the end of July 1963. The terms of reference of the committee were to make a critical review of the progress of the family planning programme in the Third Plan, the position likely to be reached at the end of this period and formulate proposals for the Fourth Plan. At the first meeting held on 29th July 1963, this Committee suggested, among other things, that ""six Appraisal Teams might be formed, each comprising Of two members and a team leader"", to assess the family planning programme in each State and the Centre.
Extracted from the Evaluation of the Family Planning Programme, Reports of Assessment Teams and the Panel of Consultants/Programme Evaluation Organization, Planning Commission, Government of India, 1965